2021
DOI: 10.1002/adma.202106624
|View full text |Cite
|
Sign up to set email alerts
|

Lateral Fully Organic P–N Diodes Created in a Single Donor–Acceptor Copolymer

Abstract: P–N junctions exist in many solid‐state organic devices, such as light‐emitting diodes, solar cells, and thermoelectric devices. Creating P–N junctions by bulk chemical doping in a single organic material (like silicon doped by boron and phosphorus) may capitalize the vast scientific and technological groundwork established in the inorganic semiconducting field. However, high‐performance single‐organic‐material P–N junctions are seldom reported, because the diffusion of the dopant counterions often leads to tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 64 publications
1
20
0
Order By: Relevance
“…To further investigate the interaction between semiconduc tors and dopants, and based on the mechanism that has been reported, [2,[81][82][83] we speculate a plausible reaction mechanism for the FeCl positions that could interact with Fe 3+ . Due to the difficulty in locating these positions on the regiorandom PRF, we set X = F and Y = H as examples in Figure 1b and analogized the rest situations accordingly.…”
Section: Resultsmentioning
confidence: 88%
“…To further investigate the interaction between semiconduc tors and dopants, and based on the mechanism that has been reported, [2,[81][82][83] we speculate a plausible reaction mechanism for the FeCl positions that could interact with Fe 3+ . Due to the difficulty in locating these positions on the regiorandom PRF, we set X = F and Y = H as examples in Figure 1b and analogized the rest situations accordingly.…”
Section: Resultsmentioning
confidence: 88%
“…38 Nevertheless, a massive gap still exists in contrast to p-type OTEs, [39][40][41] especially the ineluctable n-doping procedure which largely restricts the development of desirable n-type organic semiconductors. [42][43][44][45] Actually, the polarity (or the sign of S) of the conducting polymers does not entirely depend on the classication of chemical doping (i.e., p-or n-doping), [46][47][48] since the dominating charge carriers that are associated with the conduction can be inuenced by numerous variables, including temperature, pressure, charge transfer models and doping levels. [49][50][51][52] For example, Shuai et al, demonstrated that the temperaturedependence of S exhibits diverse tendencies differentiated by one-or two-band charge transfer models, leading to the sign of S covering both positive and negative along with the varying temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, a very high PF of 20.7 AE 0.7 mW m À1 K À2 was achieved by PIDT-HTBTDF with 0.3 M FeCl 3 , which represents the highest value of n-type OTEs by a simple pdoping technique. 47,48,52,54…”
Section: Introductionmentioning
confidence: 99%
“…Besides, the excessive p-type doping could be applied in n-type OSC materials. 67,173–175 The strong oxidant, FeCl 3 was used to dope p-type semiconducting polymer PDPP-4T, and the Seebeck coefficients changed from positive (p-type) to negative (n-type) with increasing doping levels, which might be attributed to the switch of dominant charge carriers from the hole to electron, and transporting modes from hopping to band-like. The high n-type power factor of 9.2 μW m −1 K −2 achieved in this doped system would make this unique doping way very attractive in developing air-stable n-type doped OSCs.…”
Section: Discussionmentioning
confidence: 99%